A non‐isolated symmetrical design of voltage lift switched‐inductor boost converter with higher gain and low voltage stress across switches - Md Samiullah (16888767) (2022)
The DC–DC converters have to be characterized by high gain, low voltage stress, small size, and high efficiency for most of the applications including fuel cell and photovoltaic integration to microgrid. However, conventional, quadratic, interleaved, three‐level and cascaded boost converters are not able to satisfy the requirements. This letter proposes a new, non‐isolated DC–DC converter with switched‐capacitor and switched‐inductors that can achieve high‐gain, wide‐ranging input‐voltage, and low‐voltage stress across the switches. This paper analyses the operating principle, the design of component parameters and comparisons with other high‐gain converters. Experimental results for 22 V/400 V, 50 kHz prototype finally verifies the proposed converter with a voltage gain of 19. Other Information Published in: IET Power Electronics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/pel2.12433